Development of Secure Cloud Based Storage Using the Elgamal Hyper Elliptic Curve Cryptography with Fuzzy Logic Based Integer Selection - Pandian, A. Pasumpon (Journal of Soft Computing Paradigm, 2020)
The technological advancements in the field of the information and communication technology led to the development of more promising cloud paradigm that allows online provision of services such as platform, software and infrastructure. The infrastructure services provided by the cloud allows the user data to be stored and accessed ubiquitously unlike the arrays that are available on the premises. However the security of the data that are being stored in the internet are still under research. This remains as major inhibitor for the adoption of cloud service in spite of its reliability, elasticity, high computational capabilities and the pay as you go possibilities. So the paper puts forth the construction of a secure storage as service in the cloud computing by utilizing the cryptography system based on Elgamal. The proposed method encrypts the data to be stored using the Elgamal that incorporates the hyper elliptic curve cryptography for twofold encryption and further utilizes the fuzzy logic to perform the integer selection that serves as the significant attribute in defining the cloud storage security. The point addition and the double based ECC is used for generating the keys for the hyper elliptic curve cryptography. The twofold security model put forth is validated using the MATLAB on the terms of efficiency observed on securing the data stored in cloud as well as the cost and the execution time endured by the proposed twofold security. The results shows that the protection offered by the twofold security is much better compared to the prevailing.
Keywords: Cloud Paradigm; Storage as Service; Security Challenges; Two Fold Security; Elgamal; HECC; Fuzzy Logic